.NET internationalization : the developer's guide to building global Windows and Web applications - Smith-Ferrier, Guy (Microsoft .NET development series., 2006)
As business becomes more and more global, software developers increasingly need to make applications multi-lingual and culturally aware. The .NET Framework may well have the most comprehensive support for internationalization and globalization of any development platform to date, and .NET Internationalization teaches developers how to unlock and utilize that support. Experienced international application developer Guy Smith-Ferrier covers the internationalization of both Windows Forms and ASP.NET applications, using both Versions 1.1 and 2.0 of the .NET Framework. Smith-Ferrier not only teaches you the best ways to take advantage of the globalization and internationalization features built in to the .NET Framework and Visual Studio, he also provides original code to take globalized applications to the next level of international utility and maintainability. Key topics include - An introduction to the internationalization process and how localization and globalization are supported in Windows and the .NET Framework - The use of resource managers, cultures, resource DLLs, and localized strings, images, and files-including strongly typed resources - Detailed coverage of form localization in Windows Forms and Web Forms - Dealing with regional cultures and their casing, collation, and calendars - Managing right-to-left Middle-Eastern text and pictographic East Asian languages - How to use the book's original resource administration utilities - How to translate resources with machine translation - How to create custom cultures and integrate them with the .NET Framework 2.0 and Visual Studio 2005 - How resource managers work and how to write custom resource managers, including a resource manager that uses a database - How to test your internationalization with FxCop using new and existing globalization rules - How to effectively include the translator in the internationalization process Whether you are a developer, architect, or manager, if you are involved in international applications with the .NET Framework, this is the one book you need to read and understand before you start development. Guy Smith-Ferrier is an author, developer, trainer, and speaker with more than 20 years of software engineering experience. He has internationalized applications in four development platforms, including the .NET Framework. A frequent conference speaker, Guy is the author of C# and .NET courseware and has written numerous articles ...